From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Photocatalytic degradation of Azo dyes using Au:TiO2, gamma-Fe2O3:TiO2 functional nanosystems - Jagadale, Tushar C.; Kulkarni, Manjusha; Pravarthana, D.; Ramadan, Wegdan; Thakur, Pragati (Journal of Nanoscience and Nanotechnology, 2012)
We report photocatalytic degradation studies on Navy Blue HE2R (NB) dye on significant details as a representative from the class of azo dyes using functional nanosystems specifically designed to allow a strong photocatalytic activity. A modified sol-gel route was employed to synthesize Au and gamma-Fe2O3 modified TiO2 nanoparticles (NPs) at low temperature. The attachment strategy is better because it allows clear surface of TiO2 to remain open for photo-catalysis. X-ray diffraction, Raman and UV-VIS spectroscopy studies showed the presence of gold and iron oxide phases along-with the anatase TiO2 phase. TEM studies showed TiO2 nanocomposite particles of size similar to 10-12 nm. A detailed investigation on heterogeneous photocatalytic performance for Navy Blue HE2R dye was done using the as-synthesized catalysts Au:TiO2 and gamma-Fe2O3:TiO2 in aqueous suspension under 8 W low-pressure mercury vapour lamp irradiation. Also, the photocatalytic degradation of Amranth and Orange G azo dyes were studied. The surface modified TiO2 NPs showed significantly improved photocatalytic activity as compared to pure TiO2. Exposure of the dye to the UV light in the presence of pure and gold NPs attached TiO2 catalysts caused dye degradation of about similar to 20% and similar to 80%, respectively, in the first couple of hours. In the presence of gamma-Fe2O3 NPs attached TiO2, a remarkable similar to 95% degradation of the azo dye was observed only in the first 15 min of UV exposure. The process parameters for the optimum catalytic activity are established which lead to a complete decoloration and substantial dye degradation, supported by the values of the Chemical Oxygen Demand (COD) similar to 93% and Total Organic Carbon (TOC) similar to 65% of the treated dye solution after 5 hours on the employment of the UV/Au:TiO2/H2O2 photocatalytic process.
Keywords: Azo Dye; COD; H2O2; Photocatalysis; TiO2